Penelitian Perpustakaan Digital di Perpustakaan Sekolah era Covid-19 Sebuah Narrative Literature Review - Novani, Laeli (Pustabiblia: Journal of Library and Information Science, 2023)
Covid-19 has now spread rapidly throughout the world, many impacts have oc- curred since the existence of Covid-19 in various sectors, especially in the education sector. In Indonesia, many school children find it difficult with the policies issued by the government regarding the implementation of online learning because of the limited media to support the learning process. For this reason, media such as digital libraries are needed as a source of knowledge and student learning so that the teaching and learning process can run optimally. The purpose of this study is to find out digital library research in school libraries in the Covid-19 era through analysis on digital library activities in school libraries, research methods used in research, and also the type of school library. The author uses a narrative literature review research method using several references obtained from the Google Scholar database with a range of publications from 2013 to 2022. The results of this study indicate that digital library activities in school libraries are very useful in the teach- ing and learning process during the pandemic and many schools who designs and develops a web-based digital library. As for the analysis of the research methods on the references studied, many of them used descriptive qualitative and quantitative methods. Then the type of school library used is based on references, namely using a website-based digital library or application. Digital libraries can support the online learning process and can be accessed anywhere and anytime.